PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DEPARTEMENT SECURITY SERVICE PT. ISS INDONESIA AREA PT. ALCON BATAM - Nduru, Ambrosius; Hendriati, Yossi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The research aims to find out the influence of leadership style, motivation, and work discipline on employee performance at the Security Service Department of PT. ISS Indonesia (Area PT. Alcon Batam). In this research, a quantitative method was used in which data were obtained from survey results and questionnaire data processing based on statistical procedures. Based on population studies, the sample in this study was 35 respondents. In this study, the results of the regression equation Y =-0.861 + 0.330X1 + 0.514X2 + 0.013X3 + e. Leadership style variable has an influence on employee performance with tcount (2.265) > ttable (2.03951), motivational variable has an influence on employee performance with tcount (3.554)> ttable (2.03951), work discipline variable has no effect on employee performance with a value of tcount (0.097) < ttable (2.03951), and variables of leadership style, motivation, and work discipline have an effect simultaneously by showing the calculation results of Fcount (39.551) > Ftable (2.91). While the R2 value is 0.793 or 79.30% which indicates that the independent variables (X1, X2, X3) affect the dependent variable (Y) by 79.30%, while the remaining 20.70% is influenced by other variables outside this study.